Réponses

2014-10-21T11:56:12+02:00

Pour le a c'est : 3x+8 = 2x-5

                          3x-2x=-5-8

                          1x= -13

                           x= -13

2014-10-21T12:14:58+02:00


Exercice N°1 :

a. 3x + 8 = 2x - 5

    3x + 8 - 8 = 2x - 5 - 8

    3x = 2x - 13

    3x - 2x = 2x - 13 - 2x

    x = 13


b. (2x + 3) (-5x + 1) = 0

     -10x² + 2x - 15x + 3 = 0

     -10x² - 13x + 3 = 0

     -10x² - 13x + 3 - 3 = 0 - 3

     -10x² - 13x = - 3

      x = 15


c. -2 (3x + 25) = x + 10

    -6x - 50 = x + 10

    -6x - 50 + 50 = x + 10 + 50

    -6x = x + 60

    -6x - x = x + 60 - x

    -7x = 60

    -7x /7 = 60/7

     x = 60/7


d. 4 - (x - 5)² = (x + 4)² + 37

    4 - (x² - 10x + 25) = (x² + 8x + 16) + 37

    4 - x² + 10x - 25 = x² + 8x + 16 + 37

    - x² + 10x - 21 = x² + 8x + 53

    - x² + 10x - 21 + 21 = x² + 8x + 53 + 21

    - x² + 10x = x² + 8x + 74

    - x² + 10x - 10x = x² + 8x + 74 - 10x

    - x² = x² - 2x + 74

    - x² - x² = x² - 2x + 74 - x²

    - 2x² = - 2x + 74

    -2x² = - 2x + 74

     x² = 37


e.  (2x - 1)² - 4 = 0

     4x² - 4x + 1 - 4 = 0

     4x² - 4x - 3 = 0

     4x² - 4x - 3 + 3 = 0 + 3

     4x² - 4x = 3

     x² = 3/4


f.   (3x - 1)² - (x + 2)² = 0

     9x² - 6x + 1 - (x² + 4x + 4) = 0

     9x² - 6x + 1 - x² - 4x - 4 = 0

     8x² - 10x - 3 = 0

     8x² - 10x - 3 + 3 = 0 + 3

     8x² - 10x = 3

Merci ! Sauf que pour le d c'est -37 et pas +37